PENGARUH EFIKASI DIRI, EKSPEKTASI PENDAPATAN DAN LINGKUNGAN SOSIAL TERHADAP KEPUTUSAN BERWIRAUSAHA - Qustolani, Asep; Dewi Jannati, Eidelweis; Aswati, Ninda (Jurnal Ekonomi Bisnis Kompetif, 2025)
Abstract: During the post-pandemic economic recovery period, people in Majalengka Regency are still experiencing difficulties in finding work. So that the entrepreneurial decisions are very important things to do, because with entrepreneurial decisions it can reduce unemployment. Entrepreneurial decisions to be realized are influenced by various factors such as self-efficacy, income expectations and social environment. This study aims to determine the effect of self-efficacy, income expectations and social environment on entrepreneurial decisions in Culinary Business Actors in Majalengka Regency. The method used in this study is a survey method using a descriptive and verification analysis approach. The population in this study were Culinary Business Entrepreneurs in Majalengka Regency, with a sample of 107 respondents. The sampling technique used in this research is Simple Random Sampling. The data collection technique in this study was using a questionnaire with a Likert scale. Analysis of the data used in this study is the classical assumption test, multiple linear regression analysis, the coefficient of determination, model feasibility test and hypothesis testing using the t test. The results of the research that has been done show that Self-Efficacy has a positive and significant effect on Entrepreneurial Decisions, Income Expectation has a positive and significant effect on Entrepreneurial Decisions, and the Social Environment has a positive and significant effect on Entrepreneurial Decisions.